Programa cuentos ecológicos para mejorar la conservación del medio ambiente en las niñas del segundo grado de la Institución Educativa N° 81007 Modelo – Trujillo, 2017 - Arroyo Huamán, Milagros Fiorella (2018)
The present research work entitled "PROGRAM ECOLOGICAL TALES TO IMPROVE THE CONSERVATION OF THE ENVIRONMENT IN GIRLS OF THE SECOND DEGREE OF THE EDUCATIONAL INSTITUTION N ° 81007 MODEL - TRUJILLO, 2017", has as general objective, to determine if the program ecological stories improves the conservation of the environment in the girls of the second grade of the Educational Institution N ° 81007 Model._x000D_ We worked with a sample of 60 girls of the second grade, selected with non-probabilistic sampling for convenience. The quasi-experimental design was used, with an experimental group and a control group with pretest and posttest._x000D_ The ecological story program was constituted by 16 sessions in each session the performance of the EBR Social Personnel Curriculum was developed. The questionnaire was applied to improve the conservation of the environment, where four dimensions of water, air, soil, plants and animals were evaluated._x000D_ It was concluded that the ecological story program significantly influences girls of the second grade of Educational Institution N°. 81007 Modelo - Trujillo.